Referral Uptake from School Eye Screening Program Conducted at Moradabad (India) - Pradeep Agarwal; Ashi Khurana; Veenu Maan; Samir Sutar; Lokesh Chauhan (Delhi Journal of Ophthalmology)
Purpose: The purpose of this study was to report the follow-up rate and outcome of school children who failed visual screening conducted at school. Methods: A cross-sectional study using school-based eye screenings in children aged 5–16 years from 103 schools in Moradabad, India, was conducted. Convenience sampling was done for the selection of schools. Primary vision assessment was done by a vision technician and refraction by the optometrist. All reported children were assessed by a pediatric ophthalmologist. Results: Of the 45,680 children included in the study, 26,046 (48.3%) were girls. Of all, 6% were referred for further examination. A total of 395 (14.1%) children were reported for further examination. Major barriers were: parents were not interested (356; 12.7%), time concerns (195; 6.9%), no specific reason (62; 2.2%), no one to accompany (49; 1.8%), and cannot afford travel cost (27; 1%). Of all reported, 102 (25.8%; “53 females; 49 males”) children were emmetropic, 217 (54.9%; “124 females; 93 males”) had a refractive error, and 76 (19.2%) had other eye diseases. Conclusion: Follow-up rates in children referred from school-based eye screening remain challenging. Interventions to improve follow-up rates should be incorporated during the planning of these programs. Monitoring and reporting of these programs need to be improved.